2019
DOI: 10.3329/bjp.v14i1.38089
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-oxidant, hypotensive and diuretic activities of Origanum glandulosum in rat

Abstract: In vitro anti-oxidant, hypotensive and diuretic activities of Origanum glandulosum in rat BJP Thus, much attention has been paid to the study of medicinal plants, including the screening of natural bioactive compounds such as phenolic compounds with the ability to cure, prevent the progression of many diseases (Yadegarinia et al., 2006) and the exploration of traditional medicines may reveal new treatment options to increase the therapeutic arsenal by the discovery of novel medicines and to offer lower cost al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The obtained results may be due to the presence of polyphenols and flavonoids which have the principal contribution to the antioxidant capacity of fruits extracts. In fact, literature showed that good correlation was found between antioxidant activity and the content of polyphenols and flavonoids contents 19,29 . Albano and Miguel 30 reported that flavonoids and phenolic acids are more effective in scavenging free radicals after extraction with moderate or hydrophilic solvents.…”
Section: Hydroxyl Radical Scavenging Activitymentioning
confidence: 99%
“…The obtained results may be due to the presence of polyphenols and flavonoids which have the principal contribution to the antioxidant capacity of fruits extracts. In fact, literature showed that good correlation was found between antioxidant activity and the content of polyphenols and flavonoids contents 19,29 . Albano and Miguel 30 reported that flavonoids and phenolic acids are more effective in scavenging free radicals after extraction with moderate or hydrophilic solvents.…”
Section: Hydroxyl Radical Scavenging Activitymentioning
confidence: 99%
“…Hydroxyl free radicals have been implicated in the etiology of much pathology and eventually resulted in the cell injury/death. Therefore, the scavenging of hydroxyl radicals by extracts may provide a significant protection to biomolecules against free radicals 25 .…”
Section: Hydroxyl Radical Scavenging Activitymentioning
confidence: 99%